Enhanced classroom opportunities through a focus approach: English language teaching and learning - Tiu, Glendora V. (Animo Repository, 2012)
Provision of opportunities in the classroom is one good approach in helping all language learners. These opportunities direct the exchanges and flows of communication between and among learners as well as its practical application to real life situations. One specific intervention approach created based on the value of opportunities is FOCUS Intervention Approach. This approach has been utilized in a private high school in Manila, Philippines to help and assist both teachers and learners regarding English Language Teaching and Learning. It combines the traditional and modern ways of teaching and learning English. This approach highlights four components namely Grammar, Literature, Speech and Research covering and encompassing all macro skills of reading, listening, speaking and writing. It comes with various forms featuring lesson plans highlighting the components' goals, strategies-to-use, perceived activities in context, evaluative techniques and reinforcing tasks.